Thalassemic DNA-Containing Red Blood Cells Are under Oxidative Stress. (4th March 2012) - Dana, Mutaz; Prus, Eugenia; Fibach, Eitan
Abstract : We studied the nature of enucleated RBCs containing DNA remnants, Howell-Jolly (HJ) RBCs and reticulocytes (retics), that are characteristically present in the circulation of thalassemic patients, especially after splenectomy. Using flow cytometry methodology, we measured oxidative status parameters of these cells in patients with β -thalassemia. In each patient studied, these cells had higher content of reactive oxygen species and exposed phosphatidylserine compared with their DNA-free counterparts. These results suggest that oxidative stress in thalassemic developing erythroid precursors might, through DNA-breakage, generate HJ-retics and HJ-RBCs and that oxidative stress-induced externalization of phosphatidylserine is involved in the removal of these cells from the circulation by the spleen, a mechanism similar to that of the removal of senescent RBCs.